Sociality modulates nutritional carrying capacity of an endangered species - Rankins, Seth T.; Stephenson, Thomas R.; Monteith, Kevin L. (Frontiers in Ecology and Evolution, 2024)
Group living has well-known costs and benefits. Large groups may experience greater competition for resources, while simultaneously benefit from reduced risk through predator dilution. When there is a tradeoff between forage acquisition and predation risk, the ability to congregate into large groups may unlock access to previously unavailable habitat with high risk of predation, thereby increasing forage available to the population. We evaluated whether forage availability increased with population size and how it was mediated through changes in group size. There was a tradeoff between forage availability and predation risk. Larger groups used areas with more forage biomass and greater predation risk than smaller groups. Group size also increased with population abundance, meaning bighorn sheep used gentler terrain and areas with more forage biomass at greater population abundance. Group size functionally increased carrying capacity by yielding access to more resources for growing populations of gregarious ungulates.